초등 교사를 위한 ADHD 아동 교수법 코칭 프로그램 개발 및 효과 - 박신정; 박완주; Park, Shin Jeong; Park, Wan Ju (Journal of Korean Academy of Nursing, 2017)
Purpose: The aim of this study was to identify the effects of a newly developed instructional coaching program regarding Attention Deficit Hyperactivity Disorder (ADHD) for teachers. Methods: Seventy teachers participated in this study involving a nonequivalent control group and a pretest-posttest design. The instructional coaching program consisted of eight 60-minute sessions. The program was developed through a theoretical development program involving six steps. To evaluate the effects of the program, data were collected through self-report questionnaires including the Knowledge Scale of Attention Deficit Disorder, Attitude Scale of Primary School Teachers Experiencing Students with ADHD, Practice Scale of Educational Intervention Activity, and the Korean ADHD Rating Scale. Data were analyzed with an independent t test, a chi-square test, and an ANCOVA using SPSS WIN version 20. Results: The intervention program consisted of 3 sectors, 8 subjects, and 24 content items. The experimental group showed a significant improvement in attitudes toward ADHD (F=22.83, p<.001). In addition, teacher's knowledge regarding ADHD (F=7.16, p=.010) and the implementation of instructional interventions (F=4.29, p=.043) improved. Further, teachers reported a reduction in children's ADHD-related behavior (F=4.34, p=.041). Results showed that the coaching program made a positive contribution to teaching skills and understanding of school-age children with ADHD. Conclusion: The instructional coaching program was well structured and significantly improved not only teachers'attitudes, knowledge, and teaching skills but also the behavior of children with ADHD in class. Therefore, the program is recommended as a means of facilitating teaching and managing children with ADHD in class.